Erosion or decay? Conceptualizing causes and mechanisms of democratic regression. Issue 1 (2nd January 2021) - Gerschewski, Johannes
ABSTRACT: Democratic regression has become a worrying phenomenon in the last years. Social science has provided a variety of explanations why democratic regimes have lost democratic regime quality. Against this backdrop, I take stock of the recent literature by putting forward two important analytical distinctions that we should make more explicit. First, I propose to classify our current explanations along the source where the cause for the malaise originated. By doing so, I introduce a distinction between erosion and decay type of arguments. While the former is a gradual process that is caused exogenously – like wind or water hitting a stone – the latter is caused endogenously – like the half-life in nuclear decay processes. Second, I draw a distinction between the endogenous or exogenous roots of the cause and the subsequent causal mechanism that connects the cause with the outcome. I outline the need for dissecting a causal mechanism into its constitutive components and highlight its underlying dimensions of temporality. Throughout the article, I use empirical case material as well as relevant secondary literature to illustrate these points.